2013
DOI: 10.3109/14397595.2013.850182
|View full text |Cite
|
Sign up to set email alerts
|

Correlations among enthesitis, clinical, radiographic and quality of life parameters in patients with ankylosing spondylitis

Abstract: Enthesitis was found to be associated with higher disease activity, higher fatigue, worse functional status and lower disease duration. As enthesitis was correlated with BASDAI, we conclude that enthesitis can reflect the disease activity in patients with AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
4
18
0
Order By: Relevance
“…In SpA patients with enthesitis, a significantly higher frequency of tender and swollen joint counts as well as more inflammatory axial symptoms have been found . Studies in ankylosing spondylitis (AS) patients revealed a correlation between enthesitis and higher disease activity (measured by the Bath Ankylosing Spondylitis Disease Activity Index [BASDAI]) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In SpA patients with enthesitis, a significantly higher frequency of tender and swollen joint counts as well as more inflammatory axial symptoms have been found . Studies in ankylosing spondylitis (AS) patients revealed a correlation between enthesitis and higher disease activity (measured by the Bath Ankylosing Spondylitis Disease Activity Index [BASDAI]) .…”
Section: Discussionmentioning
confidence: 99%
“…Pain is one of the consequences of enthesitis, and the current study demonstrated an association between the presence of enthesitis and higher pain scores. Rezvani et al found a positive correlation between enthesitis to the fourth question in the BASDAI questionnaire (level of discomfort from any areas tender to touch or pressure) that refer to entheseal pain among 421 AS patients. Additional support for this point derives from studies in juvenile patients with enthesitis‐related arthritis (ERA) .…”
Section: Discussionmentioning
confidence: 99%
“…The Win Pepi version 11.65 was used to calculate sample size; aiming to yield a 80% power to estimate the correlation of the enthesitis indices with disease activity scores and accepting a 5% margin of error, 109 subjects (55 with axial SpA and 54 with peripheral SpA) were deemed necessary [34]. The mean of the correlation coefficient (0,372) from previous work which studied correlation of MASES and SPARCC with BASDAI in AS was used to estimate the sample size of axial SpA since AS is the prototype of axial SpA [5,8,14,15]. The mean of the correlation coefficients obtained by Healey et al in their work which studied correlation of DAS 28 ESR with MASES and LEI (0.374) was used to estimate the number of subjects with peripheral SpA [16].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with enthesitis present higher disease activity, disability and incapacity to work, frequently associated with a poorer quality of life [4][5][6][7][8][9]. In Brazilian patients, enthesitis was strongly associated with a more severe clinical picture, including axial as well as peripheral manifestations as well as higher Bath Ankylosing Disease Activity Index (BASDAI) [4,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation